Exercise-Induced Cardiac Fatigue in Recreational Ultramarathon Runners at Moderate Altitude: Insights From Myocardial Deformation Analysis - Wolff, Sebastián; Picco, José M.; Díaz-González, Leonel; Valenzuela, Pedro L.; Gonzalez-Dávila, Emanuel; Santos-Lozano, Alejandro; Matile, Pablo; Wolff, David; Boraita, Araceli; Lucia, Alejandro (Frontiers in Cardiovascular Medicine, 2022)
Background Controversy exists on the actual occurrence of exercise-induced cardiac fatigue (EICF) with ultraendurance exercise, as well as on whether factors such as age or training status might predispose to this condition. The present study aimed to assess the occurrence of EICF among recreational ultramarathon runners, as well as to determine potential predictive factors. Methods Nineteen male recreational runners (42 ± 12yrs) participated in a 55-km trial race at moderate altitude (1,800–2,500 m). Participants were evaluated before and after the race using Doppler echocardiography and myocardial deformation analysis. EICF was determined as a reduction >5% of either left ventricular global longitudinal strain (LVGLS) or right ventricular free wall strain (RVFWS). Demographical (age, body mass index), training (training experience, volume and intensity), competition (finishing time, relative intensity) and biochemical variables (blood lactate, creatine kinase [CK] and CK-MB) were assessed as predictors of EICF. Results A significant reduction in LVGLS (20.1 ± 2.1% at baseline vs. 18.8 ± 2.4% at post-race, p = 0.026), but not in RVFWS (27.4 ± 7.0 vs. 24.6 ± 5.3%, p = 0.187), was observed after the race. EICF was present in 47 and 71% of the participants attending to the decrease in LVGLS and RVFWS, respectively. No associations were found between any of the analyzed variables and EICF except for age, which was associated with the magnitude of decrement of RVFWS (r = 0.58, p = 0.030). Conclusions Ultramarathon running at moderate altitude seems to induce EICF in a considerable proportion of recreational athletes.